2017
DOI: 10.1103/physrevb.96.205127
|View full text |Cite
|
Sign up to set email alerts
|

Topological edge-state engineering with high-frequency electromagnetic radiation

Abstract: We outline here how strong light-matter interaction can be used to induce quantum phase transition between normal and topological phases in two-dimensional topological insulators. We consider the case of a HgTe quantum well, in which band inversion occurs above a critical value of the well thickness, and demonstrate that coupling between electron states and the E field from an off-resonant linearly polarized laser provides a powerful tool to control topological transitions, even for a thickness of the quantum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…In most of theoretical studies of Floquet topological materials, [57][58][59][60][61][62][63][64][65] an electron-light interaction is introduced exclusively by employing the Peierls phase transformgiven by the replacement of a Bloch momentum k by k + A(t) -, and effects of interband electric-dipole transitions are assumed to be negligibly small under the offresonant conditions that ω = E g or ω E g ; 43,45,64 the atomic units are used. Here, A(t) and E g represent a vector potential of the laser at t, and a bandgap of the concerned material, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In most of theoretical studies of Floquet topological materials, [57][58][59][60][61][62][63][64][65] an electron-light interaction is introduced exclusively by employing the Peierls phase transformgiven by the replacement of a Bloch momentum k by k + A(t) -, and effects of interband electric-dipole transitions are assumed to be negligibly small under the offresonant conditions that ω = E g or ω E g ; 43,45,64 the atomic units are used. Here, A(t) and E g represent a vector potential of the laser at t, and a bandgap of the concerned material, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the Floquet engineering of topological surface states (Floquet topological insulators) attracts attention as an effective tool to control their physical properties. Particularly, it is shown that the irradiation with a high-frequency electromagnetic field induces topological edge states in graphene 31,32 and semiconductor quantum wells 33,34 . Optically induced Weyl points have been predicted in topological insulators and Dirac semimetals [35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the idea of utilizing off-resonant pumping to drive low-dimensional electronic systems to nontrivial topological phases has also been pushed forward [50][51][52][53][54] . For high-frequency electromagnetic fields the real processes of photon absorption or emission cannot occur because of the constraints imposed by the energy conservation.…”
Section: Introductionmentioning
confidence: 99%